Child First Developing a New Youth Justice System - Case, Stephen; Hazel, Neal. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"There is much here to reward a wide variety of readers-from those primarily concerned to develop the concepts of a Child First approach, to those seeking to apply those concepts in the front rooms of children who find themselves in trouble with the law." - Rt Hon Mark Drakeford MS, First Minister of Wales "This timely collection of essays seeks to address the challenge of providing the right help for children who find themselves in trouble...This consolidated body of learning will serve as a bulwark against any future temptation to bring large numbers of children back into the criminal justice system." - Charlie Taylor, HM Chief Inspector of Prisons for England and Wales "This book offers compelling evidence, challenging questions, and it identifies gaps and opportunities. I will be recommending the book to those researching and working in youth justice... I hope that, like me, readers will be engaged and provoked not only into thinking about the challenges but also into taking action to embed Child First in practice." - Keith Fraser, Chair, Youth Justice Board for England and Wales This book explores the development and implementation of Child First as an innovative guiding principle for improving youth justice systems. Applying contemporary research understandings of what leads to positive child outcomes and safer communities, Child First challenges traditional risk-led and stigmatising approaches to working with children in trouble. It has now been adopted as the four-point guiding principle for all policy and practice across the youth justice system in England and Wales, it is becoming a key reform principle for youth justice in Northern Ireland, and it is increasingly influential across several western jurisdictions. With contributions from academics, policymakers and practitioners, this book critically charts the progress and challenges in establishing a progressive evidence-led youth justice system. Its dynamic and accessible integration of theory, research, policy and practice, alongside discussion of critical themes, makes it a key read for students on youth crime/justice modules and for a wider market. Stephen Case is Professor of Youth Justice in the Criminology, Sociology and Social Policy division at Loughborough University, UK. Neal Hazel is Professor of Criminology and Criminal Justice in the School of Health and Society at the University of Salford, UK. .
Forewords from the First Minister of Wales, the Chief Inspector of Prisons & the Chair of the Youth Justice Board -- 1. Introduction -- Part one. Child First: Challenging youth justice systems -- 2. Challenging punitive youth justice -- 3. Challenging the risk paradigm: Children First, Positive Youth Justice -- 4. Challenging historical populism. Children First, Offenders Second: From Concept to Policy -- 5. Child First and Children's Rights: An opportunity to advance rights-based youth justice -- Part two. Child First: Developing youth justice policy -- 6. Developing Child First youth justice policy in England and Wales: A view from inside the YJB and Westminster -- 7. Developing principled youth justice standards -- 8. Child First in the criminal courts -- Part three. Child First: Developing youth justice practice -- 9. Child First: Thinking through the implications for policy and practice -- 10. The place of risk within Child First Justice: An exploration of the perspectives of youth justice practitioners -- 11. Cementing Child First in practice -- 12. Embracing children's voices: Transforming Youth Justice practice through co-production and Child First participation -- 13. Discussion and Conclusion: Future challenges and opportunities for Child First justice.
Keywords: Juvenile delinquents; Family policy; Corrections; Punishment; Social justice; Sociology; Social groups; Crime -- Sociological aspects; Youth Offending and Juvenile Justice; Children, Youth and Family Policy; Prison and Punishment; Social Justice; Sociology of Family, Youth and Aging; Crime and Society